Perlindungan Hukum Terhadap Saksi Pelaku Yang Bekerjasama (Justice Collaborator) dalam Perkara Tindak Pidana Korupsi - Antonius Yoseph Bou; I Nyoman Sujana; I Ketut Sukadana (Jurnal Analogi Hukum, 2020)
Corruption is a particular type of crime that is serious because corruption can cause economic losses to a country that threatens the continuity of development in all aspects of a country, so that an extraordinary handling is needed. The involvement of a witness as well as a perpetrator is a breakthrough that can help law enforcement officials in uncovering the complexity of criminal acts of corruption. The choice to act as a witness as well as a perpetrator who assists or cooperates with law enforcement officials is a full risk choice for that it is realized the need for a concept of protection for a witness as well as a collaborating actor so that those who are called witnesses as well as these actors can provide information needed freely without fear of threats or intimidation by parties who are directly harmed by the testimony given. Based on the description above, the issues raised will be the subject of further discussion which are deemed necessary for a learning space around the perpetrators acting as witnesses. As for those problems, namely: how is the legal arrangement for a witness who is also an actor who helps law enforcement officials in uncovering a corruption case and how the government guarantees to provide protection for witnesses and also as perpetrators in corruption cases. To answer this problem, normative research methods are used, namely by implementing a legislative approach that examines the applicable laws and regulations and adopting a conceptual approach, namely reviewing library materials in the form of theories and opinions of legal experts. Legal arrangements for a witness as well as perpetrators are regulated in a number of laws and regulations that provide the basis of guidelines for witnesses and also those who work together in disclosing corruption cases, while we can find these regulations in witness and victim protection laws. Where it provides a guarantee of legal certainty which is characteristic of the law itself because without legal certainty it is impossible to achieve legal ideals, namely the existence of justice.